A Case Report That Suggested That the Patient Was Very Sensitive to Induction and Needed 1600 mg/d of Lamotrigine to Get Therapeutic Concentrations. Issue 6 (December 2015) - Jackson, James; McCollum, Betsy; O'Neill, Amy; de Leon, Jose
Abstract : Supplemental digital content is available in the text.